Job satisfaction and affective commitment : a study of employees in the tourism industry in Sarawak, Malaysia - Yew, Tek (Sunway University College, 2007)
This study examines what motivates the employees involved in the tourism industry in Sarawak, Malaysia, their level of job satisfaction and the influence of job satisfaction on affective commitment. It also examines whether age moderates the abovementioned relationship. Tourism is a critical industry which accommodates an increasing number of visitors to Sarawak, positioning itself as the ?Sarawak-More Than A Paradise? in the Asia Pacific region. Studies have confirmed that satisfied employees will be more committed to their organizations and offer high quality service to the customers. Hierarchical regression analysis was used to analyze the data of the study. The three most important factors to motivate employees are interesting work, job security and opportunities for advancement and development. Satisfaction towards ?salary? was found to have a significant positive relationship with affective commitment. Also, satisfaction towards supervision showed significant positive relationships with normative commitment. However, age did not moderate the relationships between job satisfaction and organizational commitment. The findings of this study provide valuable insights for the management of tourism-related organizations in Malaysia and the Asia Pacific region to create a motivated and committed workforce.